Instilling Negative Stereotypes in Jackie Sibblies Drury’s Play Fairview (2018) - Anggraini, Yola; Syafei, An Fauzia Rozani (Universitas Negeri Padang, 2021)
This thesis is an analysis of the Play Fairview (2018) by Jackie Siblies Drury. The purpose of this analysis is to expose the issue of instilling negative stereotypes. It is also intended to expose how the contribution of fictional elements (character, setting, plot/conflict, and stage direction) in revealing the issue of instilling negative stereotypes. This analysis is done through text-based and context-based interpretation which are related to the concept of The Fact of Blackness by Frantz Fanon in his book Black Skin, White mask. The result of this analysis shows white has instilled the negative stereotypes toward black by circulating and perpetuating through the media that black is forever inferior.